Characteristics of outstanding public high school teachers in the Division of Quezon City as perceived by students, teachers, and administrators - Phoomchusri, Tusanee 1940- ([s.n.], 1973)
Characteristics of the teachers perceived as outstanding by high school students, teachers, and administrators are determined in this study. It specifically sought information on: the major characteristics of outstanding teachers as perceived by students, teachers and administrators, the similarities and/or differences in the perceived characteristics of an outstanding teacher, and the backgrounds of teachers who are identified as outstanding.